Implementasi Program Pembelajaran Individual Anak Berkebutuhan Khusus di PAUD - Fashlah, Anggita Gunati; Safitri, Hana Ika; Auliya, Alfiana Falan Syarri (Universitas Muhammadiyah Ponorogo, 2025)
The implementation of Inclusive PAUD cannot be separated from the existence of service programs that help all children get learning that is appropriate to their respective characteristics, one of which is through the existence of individual learning programs. This study aims to examine the implementation of the Individualized Education Program (IEP) in inclusive early childhood education, specifically at TK Negeri Pembina Banjarmasin Utara 2. The IEP is a form of educational service designed based on individual assessment results of students, particularly children with special needs (CWSN), to ensure that the learning process is effective, inclusive, and aligned with each child’s unique characteristics. The research employs a qualitative method with data collected through interviews and observations. The findings show that the school involves various stakeholders in the planning and implementation of the IEP, including classroom teachers, special education teachers, parents or guardians, and psychologists. The IEP includes assessment results, the child's identity and profile, short- and long-term learning goals, teaching methods and approaches, lesson plans, as well as evaluation and follow-up plans. The evaluation is conducted continuously and adjusted flexibly in accordance with the child's development. The IEP has proven to support an adaptive and holistic learning process and helps fulfill the educational rights of children with special needs in a fair and non-discriminatory manner.